The correlation between serum leptin and blood pressure after exposure to noise at work - Rahma, Muayad Salm; Mustafa Al-Ahmad, Basma Ezzat; Razali , Ailin; Samsuddin, Niza; Althunibat, Osama Yousef (Medknow Publications and Media Pvt. Ltd, 2013)
Several epidemiologic studies have reported that exposure to noise is associated with cardiovascular disease. The increased body weight is often associated with metabolic as well as increased blood pressure. The aim of this study is to investigate the correlation between the elevation of blood pressure and serum leptin hormones due to the effects of noise in the work place. A total of 80 volunteer males where included in this study with an age range between of 20 and 45 years, they were divided in two groups equally, the 1st group were exposed to noise in the workplace while the 2nd group were not. The individual noise exposure was determined by using a sound level meter. The range of noise was 80-100 dBA. Body Mass Index was also taken for each individual by a standard measure, blood pressure was measured by OMRON sphygmomanometer and serum leptin was measured through venous blood sample analysis enzyme linked immunosorbent assay. Spearman rank order correlation was used to examine the correlations between Blood pressure value (Systolic, Diastolic) and Leptin. All the relationships between parameters showed a positive correlation. Systolic and diastolic blood pressure values had a significant correlation to leptin hormone level in comparison to the control. There was a significant relation between leptin and blood pressure. leptin effects on the sympathetic nervous system may provide a partial explanation. Therefore, Leptin might have diverse cardiovascular actions.